Immune and genomic biomarkers of immunotherapy response in cancer of unknown primary. Issue 1 (31st January 2023) - Posner, Atara; Sivakumaran, Tharani; Pattison, Andrew; Etemadmoghadam, Dariush; Thio, Niko; Wood, Colin; Fisher, Krista; Webb, Samantha; DeFazio, Anna; Wilcken, Nicholas; Gao, Bo; Karapetis, Christos S; et al.
Abstract : Background: Cancer of unknown primary (CUP) is a heterogeneous group of metastatic cancers where a primary tissue of origin (TOO) is uncertain. Most patients with CUP have limited treatment options and poor survival outcomes. Immune checkpoint inhibitors (ICIs) can be efficacious in some patients with CUP, but the optimal predictive biomarkers are unknown. We therefore assessed immune and genomic biomarkers as well as predicted TOO in patients with CUP, including a subset treated with ICIs. Methods: Patients with CUP were subject to gene-expression profiling (GEP) and DNA panel sequencing. Immune and stromal-related gene expression was explored by NanoString, including genes associated with immunotherapy response (IR) in other solid malignancies. ICI responsive cancer types were assigned based on Food and Drug Administration-approved indications, and either detection of a latent primary tumor or the TOO was suspected based on genomics informed pathology review. Tumor mutation burden (TMB) and gene mutations were also assessed. Results: A total of 219 patients with CUP were included, 215 assessed for TOO in a previous study, with the majority (163) receiving both RNA and DNA tests. Of GEP profiled cases, 33% (59/175) had a high IR gene-expression score. Of the DNA sequenced cases, 16% (32/203) had high TMB (>10 mutations/Mb), including two with mismatch repair deficiency. Low correlation was observed between TMB and an IR score (R=0.26, p<0.001). Among 110 CUPs with a latent primary or suspected TOO, 47% (52/110) belonged to ICI-responsive cancer types. More than half of the CUPs had at least one feature that may predict ICI response (high IR score, high TMB, ICI-responsive cancer type). Among patients with CUP treated with ICIs, 8/28 (29%) responded (2 complete responses and 6 partial responses). Among non-responders, 9 had stable and 11 had progressive disease. All responders had a high IR score (7/8) and/or high TMB (3/8), while most (5/8) belonged to ICI-responsive cancer types. These features were detected at a lower frequency in non-responders and mostly in patients with stable disease. Conclusions: A significant fraction of CUP tumors had genomic features previously associated with ICI response. High IR score was the most sensitive predictive feature of ICI response, warranting evaluation in a larger patient series.